2023
DOI: 10.1021/acs.jpcc.3c00006
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation of H2 on Ag and Au Nanoparticles: Effect of Size and Plasmon versus Interband Transitions on Threshold Intensities for Dissociation

Abstract: This Article provides new insights concerning the simulation of plasmon-driven chemical reactions using real-time TDDFT based on the tight-binding electronic structure code DFTB+, with applications to the dissociation of H 2 on octahedral silver and gold nanoparticles with 19−489 atoms. A new component of these calculations involves sampling a 300 K canonical ensemble to determine the distribution of possible outcomes of the calculations, and with this approach we are able to determine the threshold for dissoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…For instance, the plasmonic excitations of Ag and Au NPs have been shown to activate carbonyl hydrogenation, dissociation of H 2 , reduction of nitroaromatics, etc. 32,[40][41][42][43][44][45] In addition, for HE-mediated processes, recent reports have suggested that interactions with semiconductors or adsorbates enhance the reaction efficiency through interfacial states. 46,47 These interfacial states provide an additional energy dissipation pathway for the plasmons or serve as transient reservoirs of these hot carriers.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the plasmonic excitations of Ag and Au NPs have been shown to activate carbonyl hydrogenation, dissociation of H 2 , reduction of nitroaromatics, etc. 32,[40][41][42][43][44][45] In addition, for HE-mediated processes, recent reports have suggested that interactions with semiconductors or adsorbates enhance the reaction efficiency through interfacial states. 46,47 These interfacial states provide an additional energy dissipation pathway for the plasmons or serve as transient reservoirs of these hot carriers.…”
Section: Introductionmentioning
confidence: 99%
“…To study the photo-dissociation of small molecules in the presence of an Au nanoparticle, the jellium model has previously been applied which treats the nanoparticle as a uniform charge density to reduce the computational cost . Other theoretical methods that explicitly consider the nuclei have also been considered. Time-dependent density functional theory (TDDFT) has been employed to study plasmon-enhanced photocatalysis with small nanoparticles. Computational methods with less expensive costs (i.e., TD-DFTB and TDDFT + TB , ) have been developed to deal with larger-sized nanoparticles. In addition, mixed levels of computational methods have been used to study the plasmon-induced H 2 dissociation on a Au(111) slab, in order to reach a balance between computational accuracy and cost …”
Section: Introductionmentioning
confidence: 99%
“…Though this is a higher field strength than most experimental CW fields, this compensates in part for the short duration of the field application. Moreover, previous work has shown that smaller nanoclusters typically require stronger applied fields for adsorbate activation, but this decreases with increasing cluster size. , For RT-TDDFT calculations, the electronic step is set to 0.002 fs. For the Ehrenfest dynamics, the electronic step size is 0.00025 fs and the nuclear step size is 0.1 fs, and the initial velocity of all the systems is set as zero.…”
Section: Introductionmentioning
confidence: 99%
“…− plasmonic mode has a smaller transition dipole moment than that of the large metal nanoparticles used in experiments. 5,15 The isotope effects provide additional insights into the role of the nuclear quantum effects. As also shown in Figure 2, when H 2 is replaced by D 2 , both RT-Ehrenfest dynamics (dashed black) and RT-NEO-TDDFT (dashed red) predict no .50 for the classical and NEO calculations, respectively.…”
mentioning
confidence: 99%
“…In parallel with experimental breakthroughs, theoretical studies of plasmon-catalyzed chemical reactions, such as H 2 photodissociation, have deepened our understanding of the underlying mechanisms. , Some simulations of plasmon-driven H 2 photodissociation have propagated the nonequilibrium quantum dynamics of the electrons with real-time time-dependent density functional theory (RT-TDDFT) and evolved the classical dynamics of H 2 using Ehrenfest dynamics . This RT-Ehrenfest approach ,, relies on a mean-field approximation and neglects nuclear quantum effects .…”
mentioning
confidence: 99%